Budowanie warsztatu aktora (casus Zbigniewa Cybulskiego) - TOKARCZYK, JOLANTA (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Building the at of acting (casus Zbigniew Cybulski) 2017 brings two important anniversaries: the 90th anniversary of the birth (1927) and 50th anniversary of the death of Zbigniew Cybulski, Polands foremost actor of the 1960s and the hero of his time. His image (dark sunglasses, leather jacket, worn jeans and sneakers and ever-present backpack) was imitated by thousands of Poles. For Cybulski one of the most important means of expression were gestures. This was very important in one of Cybulskis first films - Ashes and Diamonds. Cybulski developed his arsenal of acting expression in subsequent films, including: Night Train, See you tomorrow, No more divorces, The Saragossa Manscript, Salto, The Codes, Jowita.